2013
DOI: 10.5539/jas.v5n5p148
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Resistance to Phytophthora infestans on Potato Plants in Field, Laboratory and Greenhouse Conditions

Abstract: An experiment was conducted to determine the host resistance of potato against Phytophthora infestans for twenty-five potato genotypes in 2010 and 2011 at Khumaltar, Lalitpur, Nepal using four assays: three for foliage resistance (field, whole-plant and detached leaf) and one for tuber resistance (tuber slice). An isolate of P. infestans collected from Lalitpur (LPR-1) was used for inoculation at a concentration of 3 x 10 3 sporangia ml -1 in all assays. Infected foliage area in the field and whole-plant assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…The detached leaflet method was moderately correlated with the field test, for disease severity. According to Sharma et al (2013), a moderate correlation of resistance of potato genotypes to P. infestans was also found between the detached leaflet and field trial assays. However, in this study, genotypes with high resistance in the field were identified as having a lower level of resistance in the leaflet test when it was inoculated with the more aggressive isolate, suggesting caution in the results of the detached leaflet test.…”
Section: Resultsmentioning
confidence: 96%
“…The detached leaflet method was moderately correlated with the field test, for disease severity. According to Sharma et al (2013), a moderate correlation of resistance of potato genotypes to P. infestans was also found between the detached leaflet and field trial assays. However, in this study, genotypes with high resistance in the field were identified as having a lower level of resistance in the leaflet test when it was inoculated with the more aggressive isolate, suggesting caution in the results of the detached leaflet test.…”
Section: Resultsmentioning
confidence: 96%
“…This study did not fully reflect the conditions of whole tuber infections because the standard tuber slice technique was used, which did not include initial infection through the tuber skin. However, both techniques have been reported to successfully separate resistant from susceptible potato varieties (Sharma et al ., ). Despite the lack of statistical relationship between foliar and tuber blight, the current tuber slice assay analysis did reveal variations in aggressiveness of the isolates, and it is noteworthy that the least aggressive isolates in the detached leaf assays had minimal colony sizes on the tuber slices.…”
Section: Discussionmentioning
confidence: 97%
“…The assay was adapted from the method described by Sharma et al (2013). Medium-sized potato tubers of cvs Kachpot-1 and Sarpo Mira without any visual symptoms of infection of P. infestans or other disease were harvested from the screenhousegrown plants in Uganda and used for this assay.…”
Section: Tuber Slice Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Kuhl et al (2007) juga melaporkan bahwa gen Rb dapat menciptakan ketahanan penyakit busuk daun pada kultivar kentang yang rentan. Percobaan lapangan diperlukan untuk membuktikan efektivitas gen Rb karena karakterisasi molekuler serta pengujian di tingkat laboratorium dan rumah kaca tidak menjamin munculnya fenotipe tahan di kondisi lapangan (Sharma et al 2013, Kuhl et al 2007 Perakitan varietas tahan terhadap penyakit busuk daun menjadi salah satu tujuan penting dalam pemuliaan kentang, akan tetapi seringkali klon unggul yang tahan penyakit busuk daun tidak mendapat penerimaan pasar dan konsumen, sehubungan dengan morfologi umbi. Morfologi umbi menjadi pertimbangan tersendiri oleh konsumen, termasuk untuk kepentingan industri olahan.…”
Section: Hasil Dan Pembahasanunclassified